Faktor-Faktor yang Berhubungan dengan Infeksi Soil Transmitted Helminth Pada Siswa Sekolah Dasar - Asrori, Asrori; Edyansyah, Erwin; Nurhayati, Nurhayati; Mutolib, Abdul; Karwiti, Witi; Dani, Hamril (LPPM Hang Tuah Pekanbaru, 2024)
Soil-transmitted helminth (STH) is a group of intestinal nematodes that are transmitted through the soil. STH infection can affect all ages, but the highest rate is found in elementary school children, which is 60-80%. The purpose of this study was to determine the relationship between risk factors and STH infection. This type of research is an analytical survey with a Cross-Sectional approach. Examination of worm eggs using the Kato-Katz method. The population is 197 students. The sample is public elementary school students with a total sample of 100. The inclusion criteria are grade 4 and 5 elementary school students in Lalan sub-district. The exclusion criteria are not grade 4 and 5 elementary school students in Lalan sub-district. The test was performed with a Chi-square test with an alpha of 0.05. The results of the study were 28 (28%) infected with STH. Chi-Square statistical test showed a relationship between gender (p-value 0.016, OR 3.545), the habit of defecation (p-value 0.017, OR 3.317), and the habit of using footwear (p-value 0.005, OR 13.50) with STH infection. Then there is no relationship between nail habits (p-value 0.118) with STH infection.